Pengaruh Media Pembelajaran Berbasis Augmented Reality terhadap Hasil Belajar Mahasiswa pada Matakuliah Rangkaian Listrik - Satria Buana Putra; Mukhlidi Muskhir (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The development of digital technology has changed the landscape of educational media, especially in the field of engineering, where abstract concepts often pose a challenge. In electrical engineering education, students often have difficulty understanding concepts such as current flow and circuit behavior due to limited class time and a lack of visualization tools. This study aims to evaluate the effectiveness of Augmented Reality (AR)-based learning media in enhancing conceptual understanding, learning outcomes, and student engagement in the Electrical Circuits course. A quasi-experimental design with pre-test and post-test control groups was applied, involving two groups: one group used AR-based media, while the control group used traditional instruction. Both groups underwent pre-tests and post-tests with 30 multiple-choice questions. Data were analyzed using descriptive statistics and N-Gain scores. Results showed that the experimental group experienced a significant improvement, with the average post-test score increasing from 62 to 81 and an N-Gain score of 0.48, while the control group only improved from 61 to 71 with an N-Gain score of 0.25. Statistical tests confirmed significant differences between the two groups. These findings indicate that AR is effective in enhancing understanding of complex concepts and can be integrated into technical education curricula to meet modern learning demands.